Arabic Language Learning Culture in Salaf Islamic Boarding Schools: An Ethnographic Study of Linguistic Punishment Practices and Traditions - Siregar, Rahmat Sapaat (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
This research aims to explore the traditions and behaviors related to Arabic language learning in salaf pesantren with special attention to the practice and tradition of linguistic punishment as a pedagogical strategy. Based on participation in observation, interviews, and document analysis, this study shows that Arabic is not only taught formally, but also expressed and practiced in the daily lives and identities of students. Linguistic punishments such as sentence repetition, vocabulary exercises, or public speech help learning to be more active and serve to elevate discipline and collective responsibility. This discipline also produces a new level of learning culture where language acquisition is associated with the formation of character and faith values. These findings confirm that this kind of approach should be considered in an effort to build student accountability built in a positive, immersive, sustainable, and harmonious learning environment between traditions and educational functions.